DIFFICULTIES IN LEARNING TO APPLY GENERAL SEMANTICS: TRANSCRIPT OF A RECORDING OF ALFRED KORZYBSKI. - HAUCK, BEN (ETC: A Review of General Semantics)
The article presents a transcript of a recording by Alfred Korzybski talking with his student Kenneth Reyes on difficulties in learning to apply general semantics. Topics discussed include the famous bequest of Professor Ivan Pavlov to the academic youth of his country, problems about writers and readers, and advice from mathematician Gottfried Wilhelm Leibniz for his readers and hearers.